2016
DOI: 10.1186/s12955-016-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Many correlates of poor quality of life among substance users entering treatment are not addiction-specific

Abstract: BackgroundQuality of life (QoL) is an important measure and outcome within chronic disease management and treatment, including substance use disorders (SUD). The aim of this paper was to investigate correlates of poorer QoL of individuals entering SUD treatment in Norway, in order to identify subgroups that may most benefit from different interventions.MethodsTwenty-one treatment facilities invited all incoming patients to participate. Five hundred forty-nine patients who enrolled between December 2012 and Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 49 publications
14
64
0
4
Order By: Relevance
“…Our study confirms previous research that suggests that women with COD obtain lower mean QOL scores than men [1013]. Similar to a study conducted in the US, women reported lower scores in the environmental domain [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirms previous research that suggests that women with COD obtain lower mean QOL scores than men [1013]. Similar to a study conducted in the US, women reported lower scores in the environmental domain [14].…”
Section: Discussionsupporting
confidence: 91%
“…We confirmed that women reporting traumatic events had lower scores in the physical and psychological QOL domains [14]. As previous research, depressive and anxiety disorders were associated with lower QOL mean scores [13]. …”
Section: Discussionsupporting
confidence: 88%
“…The present study is part of the larger Norwegian Cohort of OMT and other Substance Use Treatment (NorCOMT) multicenter study, the first results of which have been published elsewhere [28, 29]. In this paper, we study a subset of the NorCOMT cohort: patients who entered OMT and completed a satisfactory ASRS ( n  = 175).…”
Section: Methodsmentioning
confidence: 99%
“…Forty-one per cent had completed more than 10 years of education (mandatory level) and 11% were currently employed or under education. A more detailed description of the procedure has been given previously (Muller, Skurtveit, & Clausen, 2016;Skjaervø et al, 2017).…”
Section: Participants and Proceduresmentioning
confidence: 99%